Finite element analysis of in-plane displacements and von-mises stresses in ellipsoidal and circular cylinderical petroluem tankers (2013)
" Road tankers are the most used means of transporting petroleum product to end users due to its cost effectiveness and energy-efficiency. The cylindrical tank has been well designed for by ASME VIII divisions 1 and 2 using analytical equations. Petrol tankers are not circular but elliptical probably for stability during transportation. This paper has used the finite element method to investigate in-plane displacements and Von-Mises stresses in both circular and elliptical cylindrical tanks under full loading. An elliptical OANDO? tanker of 66.78 m3volume and shell thickness of0.2 mmand an equivalent volume circular cylindrical tank was used for the simulation. MATLAB? was used to generate geometrical mesh model of the petroleum tankers, extract element coordinates and conduct the finite element analysis. Plane strain condition was used in analyzing a section of the petroleum tanker. It was observed that an equivalent volume circular cylindrical tank was under a higher internal pressure (16,858 N/m2) compared to the elliptical cylinder (14,480 N/m2). Von-Mises stress and in-plane displacements showed direct linear relationships with internal fluid pressure. Von-Mises stress in the elliptical tank was found to be lower (5.7 × 106 N/m2) than for the circular tank (8 × 106 N/m2). In plane displacements was zero in the longitudinal direction for both tanks and of the order of 10-4 mm in the y-direction for both tanks with the circular larger by about 2.5 × 10-3 cm. So in addition to tank stability on the lorry, the Von-Mises stresses were lower as well for the elliptical tank. It was also observed that Von-Mises stresses were far below the yield stress of the steel plate. However, the effect of weldment area on lowering of yield stress was not studied. Stress values were validated using analytical method and found to be insignificantly different (P > 0.05). "